Conversores Bidirecionais como Infraestrutura para o Carregamento Rápido e Off-Board de Veículos Elétricos - BRUNO CANDIA DALLA NORA (2025)
The use of electric vehicles has expanded. With that in mind, proper charging is key to assist in the evolution of this technology, with fast charging being a differential in day use, where bidirectional power flow can be especially relevant. As such, this work has as its main goal to study and simulate DC-DC and AC-DC power converters for fast-charging of an Electric Vehicle based on Tesla’s Cybertruck model. The simulation employs parallelism and control to simulate the battery charging strategy. As a result, there were multiple current waveforms from both types of converters with parallelism in each of them, meaning higher power demands can be obtained with a single central control scheme, reducing individual power requirements for each converter cell, meaning the cost and volume for the components can be lowered. It was possible to obtain close to 254 kW from 4 NPC VSI connected to the grid, all using the adc-dq0 transformation rule with an SRF-PLL. For the Double-Active-Bridge, 4 converters generated 32kW of power each using a Single-Phase-Shift strategy. This work then concludes that central control parallelism is a valid strategy to supply an EV battery, and in future works, be implemented to reach even higher power standards.